ANALISIS EXPERIENTIAL MARKETING TERHADAP BRAND IMAGE SERTA DAMPAKNYA PADA TOURIST SATISFACTION DI KOTA BANDUNG - Mohamad Hadi Prasetyo (Universitas Islam Bandung, 2016)
Todays, there are the cities in the world trying to make the cities more beautiful and develop the tourism side to be able to reach the tourist market, because of the income of tourism sector is so potential. Not only the cities in the world but also in Indonesia do the same. Many region try to develop the strategis to involve the tourism, and one of them is Bandung City, with experiential marketing, it will impact the level of tourist satistfaction which may lead to loyalty to the city through the image formed in the minds of tourists. This study to analyzes the influence of Experiential Marketing against Brand Image and its impact on Tourist Satisfaction In Bandung.